Geometrical statistical channel model with an Inverted-Parabolic spatial distribution - Jie ZHOU; Dong-dong XU; Kikuchi HISAKAZU (Tongxin xuebao)
Due to the complexity of calculation for the parameters of angle of arrival(AOA),time of arrival(TOA) and Dopplerspectra(DS),etc.,a proper geometrical statistical channel model was proposed with inverted-parabolic spatial distribution around mobile station(MS) by using geometric partitioning method.Closed-form expressions for probability density functions(PDF) of AOA ,TOA and DS in the outdoor macrocell and microcell wireless environments were derived.Compared with the uniform and Gaussian scatter density model,the observed results consist with previous theory and experience.In addition,the Doppler spectra at the MS was also presented and the Clarke U-shaped model was modified.Employing the channel model,the effect of directional antenna was analyzed with the main-lobe width 2α at the BS and D/R and φ .v